2010
DOI: 10.1182/blood-2010-04-277707
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin-1 hemichannel–mediated ATP release together with P2X1 and P2X4 receptors regulate T-cell activation at the immune synapse

Abstract: Engagement of T cells with antigenpresenting cells requires T-cell receptor (TCR) stimulation at the immune synapse.We previously reported that TCR stimulation induces the release of cellular adenosine-5-triphosphate (ATP) that regulates T-cell activation. Here we tested the roles of pannexin-1 hemichannels, which have been implicated in ATP release, and of various P2X receptors, which serve as ATP-gated Ca 2؉ channels, in events that control T-cell activation. TCR stimulation results in the translocation of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
357
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(379 citation statements)
references
References 49 publications
8
357
1
4
Order By: Relevance
“…This suggests that spatiotemporal dynamics of mitochondrial translocation within the cell can regulate PMN functions. Indeed, similar observations were made in T cells where the accumulation of mitochondria and panx1 at the immune synapse results in the physical proximity of the sites of ATP production and of ATP release, minimizing rate-limiting diffusion and thus facilitating rapid local purinergic signaling at the immune synapse (25)(26)(27)(28)43). Thus, we conclude that mitochondrial ATP production and the location of mitochondria relative to panx1 contribute to purinergic signaling in stimulated PMNs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This suggests that spatiotemporal dynamics of mitochondrial translocation within the cell can regulate PMN functions. Indeed, similar observations were made in T cells where the accumulation of mitochondria and panx1 at the immune synapse results in the physical proximity of the sites of ATP production and of ATP release, minimizing rate-limiting diffusion and thus facilitating rapid local purinergic signaling at the immune synapse (25)(26)(27)(28)43). Thus, we conclude that mitochondrial ATP production and the location of mitochondria relative to panx1 contribute to purinergic signaling in stimulated PMNs.…”
Section: Discussionsupporting
confidence: 54%
“…Recent work by others has shown that different sets of P2 receptors regulate Ca 2ϩ signaling in other cell types (29). P2X receptors function as ATP-gated ion channels that can facilitate Ca 2ϩ influx, and in T cells, P2X1, P2X4, and P2X7 receptors regulate influx of extracellular Ca 2ϩ and cell activation in response to T cell stimulation (27,28). PMNs express several members of the P2X receptor family in addition to the predominant P2Y 2 receptor (5, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in Jurkat cells and normal human T cells have indicated that the T cell receptor (TCR) activation triggers a very rapid but transient (within minutes) release of ATP via both Panx1 channel-mediated and exocytotic pathways (33,58,59). Both ATP release mechanisms were dependent on the increase in cytosolic [Ca 2ϩ ] elicited by TCR activation.…”
Section: Dynamic Changes In the Profile Of Adenine Nucleotide Speciesmentioning
confidence: 99%
“…Moreover, most types of tumor cells per se express different cassettes of P2 purinergic or P1 adenosine receptors that can modulate cell growth, survival, and sensitivity to pro-apoptotic mediators. Indeed, the leukemic Jurkat cells used in this study express several ionotropic P2 receptor subtypes, including P2X1, P2X4, and P2X7, and these receptors act as autocrine modulators of TCR signaling pathways that regulate growth and cytokine production (58,59). It is interesting to speculate whether autocrine activation of these receptors during chemotherapeutic drug-induced Panx1 activation may also modulate apoptotic progression in Jurkat or other leukemic cells.…”
Section: Elevated Expression Of Panx1 Channels In Leukemic Versus Normentioning
confidence: 99%
“…Pannexin proteins are found in three different isoforms Panx channels have been suggested to act as paracrine release channels that are strongly implicated in the release of purine nucleotides from cells [30,154,162,165,227].…”
Section: Introductionmentioning
confidence: 99%